Efficient and Stable Mesoscopic Perovskite Solar Cells Using PDTITT as a New Hole Transporting Layer. (10th October 2019) - Tavakoli, Mohammad Mahdi; Zhao, Jiayuan; Po, Riccardo; Bianchi, Gabriele; Cominetti, Alessandra; Carbonera, Chiara; Kong, Jing
Abstract: Stability is the main challenge in the field of organic–inorganic perovskite solar cells (PSCs). Finding low‐cost and stable hole transporting layer (HTL) is an effective strategy to address this issue. Here, a new donor polymer, poly(5, 5‐didecyl‐5H‐1, 8‐dithia‐as‐indacenone‐ alt ‐thieno[3, 2‐ b ]thiophene) (PDTITT), is synthesized and employed as an HTL in PSCs, which has a suitable band alignment with respect to the double‐A cation perovskite film. Using PDTITT, the hole extraction in PSCs is greatly improved as compared to commonly used HTLs such as 2, 2′, 7, 7′‐tetrakis[ N, N ‐di(4‐methoxyphenyl)amino]‐9, 9′‐spirobifluorene (spiro‐OMeTAD), addressing the hysteresis issue. After careful optimization, an efficient PSC is achieved based on mesoscopic TiO2 electron transporting layer with a maximum power conversion efficiency (PCE) of 18.42% based on PDTITT HTL, which is comparable with spiro‐OMeTAD‐based PSC (19.21%). Since spiro‐based PSCs suffer from stability issue, the operational stability in the PSC with PDTITT HTL is studied. It is found that the device with PDTITT retains 88% of its initial PCE value after 200 h under illumination, which is better than the spiro‐based PSC (54%). Abstract : Replacing a 2, 2′, 7, 7′‐tetrakis[ N, N ‐di(4‐methoxyphenyl)amino]‐9, 9′‐spirobifluorene hole transporting layer with new alternatives such as poly(5, 5‐didecyl‐5H‐1, 8‐dithia‐as‐indacenone‐ alt ‐thieno[3, 2‐ b ]thiophene) in mesoscopic perovskite solar cells reduces the fabrication cost and improves the operational stability without sacrificing the efficiency.